Building Social Cohesion: Family, Friends, and Corruption. (September 2014) - Roman, Alexandru V.; Miller, Hugh T.
While material gain continues to be a leading motivator for corrupt acts, this study shows that social status and kinship responsibilities should also be considered possible precursors to corruption. This finding has important implications for constructing an appropriate understanding of corruption, designing anticorruption policies, and achieving ethical governance in developing democracies.